Mind wandering, control failures, and social media distractions in online learning. (April 2016) - Hollis, R. Benjamin; Was, Christopher A.
Abstract: Mind wandering often leads to performance and accuracy errors during activities that are demanding and require concentration. Students are often asked to concentrate on demanding tasks in their studies, and by the nature of this principle, off-task thinking would inherently be prohibitive to their success. Further, the distracting nature of social media and technology may greatly increase the likelihood of mind wandering when students are engaged in online learning, requiring them to engage with said technology. To examine the relationships among working memory, interest, mind wandering and performance, 126 participants from at a large Midwestern state university completed three complex span tasks, responded to mind-wandering probes while watching two online lectures and rated interest in the lecture topics. Higher levels of mind wandering predicted lower levels of academic performance. Lower levels of working memory capacity predicted higher levels of mind wandering and lower levels of academic performance. Higher levels of topic interest predicted lower levels of mind wandering. A novel mind wandering probe, thinking about or using another technology, accounted for 29% of all off-task thinking. Highlights: Subjects responded to thought probes while watching two online video lectures. We modeled relationships among mind wandering, WMC, interest and performance. Higher levels of mind wandering related to lower levels of performance. Lower levels of working memory capacity related to higher levels of mind wandering. Mind wandering about social media accounted for 29% of all off-task thinking.